Social models as dynamic theories: how to improve the impact of social and political sciences - Alexander, Titus (Frontiers in Political Science, 2025)
This paper explores the hypothesis that institutions are “dynamic social theories” that embody accumulated knowledge from everyday social experiments about how to do things in society. Institutions that are replicated, imitated or adapted act as social models and can be seen as the social science equivalent to theories in the natural sciences. In open societies they also benefit from a form of peer review by citizens in what can be seen as the “democratic method.” This hypothesis is testable and could improve the impact of social and political sciences by working with citizens, practitioners and policymakers to embed research methods into social models. Why does this matter? Humanity’s biggest and most difficult problems are social and political, yet funding and support for academic social science is a low priority while large scale social research is conducted for commercial or political purposes in ways that may not be in the public interest. By working on institutions as social experiments and models (“dynamic theories”), scholars can help improve humanity’s ability to solve social problems. The concluding discussion and Supplementary material explores practical implications and how it can be tested, starting with models of social research, higher education and democracy.